Self-Medication and Pharmaceutical Dispensing in Egypt: Practices, Policies, and Regulatory Challenges - Shaheen, Lobna Fawzy Ali (AUC Knowledge Fountain, 2026)
Access to safe and appropriate medications is a critical component of public health, particularly in low- and middle-income countries. In Egypt, self-medication and informal pharmaceutical dispensing have become deeply embedded practices shaped by systemic, economic, and cultural factors. This research explores the complex interplay between self-medication behaviors, pharmaceutical regulation, and healthcare access in Egypt. Through qualitative interviews with policymakers, pharmacists, physicians, industry professionals, and citizens, the research uncovers widespread informal dispensing of prescription-only medicines, driven by high out-of-pocket costs, limited insurance coverage, and high public reliance on pharmacists as primary care providers. Despite the presence of regulatory frameworks, weak enforcement, lack of technological and human resources, and limited public awareness hinder effective governance. The study concludes with evidence-based policy recommendations to enhance regulatory enforcement, improve healthcare access, integrate pharmacists into formal care, and strengthen public education, offering a path toward safer and more equitable medication practices in Egypt.